Correlates of school dropout and absenteeism among adolescent girls from marginalized community in north Karnataka, south India. (December 2017) - Prakash, Ravi; Beattie, Tara; Javalkar, Prakash; Bhattacharjee, Parinita; Ramanaik, Satyanarayana; Thalinja, Raghavendra; Murthy, Srikanta; Davey, Calum; Blanchard, James; Watts, Charlotte; Collumbien, Martine; Moses, Stephen; et al.
Abstract: Secondary education among lower caste adolescent girls living in rural Karnataka, South India, is characterized by high rates of school drop-out and absenteeism. A cross-sectional baseline survey (N=2275) was conducted in 2014 as part of a cluster-randomized control trial among adolescent girls (13-14 year) and their families from marginalized communities in two districts of north Karnataka. Bivariate and multivariate logistic regression models were used. Overall, 8.7% girls reported secondary school dropout and 8.1% reported frequent absenteeism (past month). In adjusted analyses, economic factors (household poverty; girls' work-related migration), social norms and practices (child marriage; value of girls' education), and school-related factors (poor learning environment and bullying/harassment at school) were associated with an increased odds of school dropout and absenteeism. Interventions aiming to increase secondary school retention among marginalized girls may require a multi-level approach, with synergistic components that address social, structural and economic determinants of school absenteeism and dropout.